From uncertainty to the experience of collective care: Immersion in a hospital COVID-19 unit during the 'first wave' of the epidemic in Marseille, France - Francesca Mininel; Marc Egrot; Kelley Sams (Elsevier, 2023)
Social and psychological risks are weighed against biological risks and addressed by healthcare workers responding to health crises. This article examines the transformation of biosecurity protocols in one hospital in Marseille, France as the beginning of the COVID-19 pandemic and how they were adapted to meet changing needs. Based on ethnographic methods that included active observation alongside caregivers, nurses, and medical doctors during their professional activities, as well as interviews with healthcare professionals and administrators, we analyze some of the key strategies used by these staff to negotiate challenges related to the uncertainty provoked by the emerging virus and changing protocols. We examine the strategies of health professionals through the lens of 'collective care' and shared decision-making to show how collaborative work practices allowed these individuals to mitigate challenges provoked by the health crisis while supporting the needs of the individuals in their care. A key recommendation that emerges from this study is the importance of favoring the cognitive, relational, and organizational aspects of collective care.